Información para la gerencia de los servicios de enfermería - Lombana Córdoba Clemencia (Universidad Nacional de Colombia, 1994)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> &